(untitled) (Research, Society and Development, 2020)
Congenital infections are the main causes of permanent disability in children and have a major impact on morbidity and mortality and treatment costs. Among the main infections that can cause complications in pregnancy are: toxoplasmosis, rubella, cytomegalovirus, syphilis, zika virus, herpes, hepatitis, acquired immunodeficiency syndrome and parvovirus B19. These infections can cause morphological changes in fetal tissues or organs, thus, early identification and treatment can reduce maternal-fetal transmission and / or decrease the impact on the fetus. Thus, the aim of this study was to conduct an updated review of congenital infections, highlighting epidemiological, diagnostic and treatment aspects. This is a literature review, and for the construction of the text, the following databases were used: Scielo, pubmed, BVS and Google academic. Therefore, prevention, early diagnosis of congenital infections and other actions aimed at the adequate treatment of women and their children, with the integration of health programs and local surveillance systems, are extremely important for public health.